Peran Guru dalam Menumbuhkan Intensi Berwirausaha pada Siswa Tuna Rungu di SMPLB Karya Mulia V Surabaya - Bambang Purnomo; Bambang Raditya Purnomo (Universitas Proklamasi 45 Yogyakarta, 2017)
This research is motivated by the lack of entrepreneurial intention of deaf students in SMPLB-B (Junior High-School for Disabled Children Type B) Karya Mulia V Surabaya, Indonesia in which so many alumni became laborers or even unemployed. Entrepreneurship intention is one of predisposition factors that determine a person's entrepreneurial behavior. One of which various aspect determines how much a person's intention to perform a behavior is the social environment in a student's life, especially teachers. This research also shows that the intention of entrepreneurship can be nurtured since an earlier age through education. As the student’s main educator, teachers play an important role in the process. This article discusses how the role of teachers through parenting is done to foster entrepreneurship intention of the students by using theories of planned behavior.